EFFECT OF PACKAGING TYPE AND STORAGE AT ROOM TEMPERATURE ON THE QUALITY OF PAPAYA DODOL - Wuri Marsigit; Marniza Marniza; Reza Febi Ayu Monica (BPFP Faperta UNIB, 2020)
The home industry mostly packs papaya dodol using PP plastic packaging. It is necessary to research the quality of papaya dodol that is stored with various types of packaging during storage. This study aims to obtain a type of packaging that is able to maintain the physical, microbiological, and organoleptic qualities of papaya dodol during storage at room temperature. The study was carried out following a completely randomized design (CRD) with two factors; namely the type of packaging with PP plastic, aluminum foil, and wax paper; and duration of storage; i.e. 7 days, 14 days, 21 days and 28 days. The observed variables included color, texture, moisture content, mold and organoleptic properties. The collected data were analyzed using ANOVA and DMRT follow-up tests. The results showed that during 28 days of storage, the best quality of dodol was packed with aluminum foil on day 21; with a color of 7.5 YR 4/4, hardness (texture) 2.00 mm / g and a moisture content of 9.65%; and microbiological observations of 180 colonies/g; which means meeting SNI requirements. Organoleptic quality based on the aroma level of 2.92 (enough likes), 2.96 colors (enough likes), texture 2.16 (dislikes) and taste 3.08 (quite likes)